Uprawnienia Policji wobec zgromadzeń - Witkowski, Tomasz (Wydawnictwo eBooki.com.pl, 2018)
The experience of the past few years teaches that securing assemblies is a major challenge for the Police and greater opportunities for influencing event organizers, but also the increasing demands placed on policemen carrying out these protections right at the assembly site. The purpose of the work is to indicate the tasks of the Police in the implementation of the Law on Assembly. The right to assembly will be discussed in the light of the Constitution of the Republic of Poland and other legal acts. The definition and essence of the assembly and the public assembly will be presented here. Characteristic will be the freedom to assembly resulting from the Constitution of the Republic of Poland. The right to assembly will be discussed in accordance with the code of offenses.
Keywords: assembly; police law in assemblies; peaceful assemblies; police surveillance in assemblies; the right of public gatherings; freedom of assembly; use of force by the police; public order of assemblies; police in assemblies; security of assemblies; security of assemblies; security of public events; security of participants of assemblies; police powers